(untitled) (Journal of Business Management and Accounting, 2020)
Women’s equality and empowerment are one of the 17 Sustainable Development Goals that was initiated to eliminate gender discrimination. This goal can be achieved through establishing women entrepreneurship by employing critical failure factor analysis. Thus, this study was aimed to explore the obstacles faced by women entrepreneurs; consisting of restricted training and education, legal constraints, limited access to financial resources, and family-related interface. Besides, this study was intended to examine how these obstacles affected women entrepreneurs’ growth. Data related to 109 women entrepreneurs’ in Malaysia were collected. The Relative Importance Index (RII) was used to rank these obstacles. Subsequently, partial least square structural equation model analysis was performed on the data. The findings revealed that restricted training and education, limited access to financial resources, and familyrelated interface have an adverse effect on women entrepreneurs’ growth. Therefore, theoretically this study offered a new women entrepreneurs model by linking the obstacles and growth within a single study.